AN (Afghanistan) v. Secretary of State for the Home Department. (2018) - Unknown
Abstract : Aliens — Refugees — Determination of refugee status — Exclusion from protection due to participation in international crimes — Convention relating to the Status of Refugees, 1951 — Interpretation — Article 1F — Whether "serious reasons for considering" appellant was complicit in war crimes — Standard of proof — Whether change of approach by UK Supreme Court in Al-Sirri material to Asylum and Immigration Tribunal decision Human rights — European Convention on Human Rights, 1950, Article 3 — Non-refoulement — Whether entitlement to additional protection under Convention relating to Status of Refugees, 1951 or EU Council Directive 2004/83/EC International criminal law — War crimes — Elements of complicity in war crimes — Whether finding of English judge that appellant complicit in war crimes correct War and armed conflict — Non-international armed conflict — Afghanistan — Whether appellant complicit in war crimes during non-international armed conflict — The law of England